Poisoning of butanol-containing products: Clinical characteristics and outcomes - Satariya Trakulsrichai (2022)
Background: Butanol (butyl alcohol) is a chemical which occurs naturally in some foods and is used in the manufacture of other chemicals. Current data on butanol poisoning in humans are limited. Objective: This study describes clinical characteristics and outcomes of patients exposed to products containing butanol. Methods: We performed a 5-year retrospective cross-sectional study by analyzing data from the Ramathibodi Poison Center Toxic Exposure Surveillance System for 2013–2017. Results: There were 163 patients included in the study. All products containing butanol reported were agricultural adjuvant products. Most (67.5%) patients were males and had ingested butanol accidentally (75.5%). The median age was 42 years. Almost all patients had oral exposure to butanol. At presentation, most of our patients had normal vital signs and were conscious. Clinical presentations mostly included gastrointestinal symptoms (65%) and local irritation (28.8%). Fifty-four patients (33.1%) had no obvious clinical effects at presentation. Most patients had normal laboratory tests at presentation, although eight developed systemic effects including high anion gap metabolic acidosis (n=8), acute kidney injury (AKI; n=5), depression of consciousness (n=5), and hypotension (n=3). Of these eight patients, two with intentional ingestion developed altered consciousness, hypotension, AKI, severe metabolic acidosis, and eventually died. One of these died within 1 day after ingestion, while the other died later through complications during admission. Therefore, the mortality rate was 1.23%. Sixty-six patients (40.5%) were admitted to hospitals, with a median length of stay of 1 day. Most patients received only supportive treatment and fully recovered. Conclusion: Agricultural adjuvant products containing butanol or butanol itself caused only mild effects in most patients, but systemic effects occurred in some. The mortality from this poisoning was very low, and both fatalities were from intentional ingestion. Supportive care and proper management of complications should be the main treatment for this form of poisoning.